Large-current-stable bifunctional nanoporous Fe-rich nitride electrocatalysts for highly efficient overall water and urea splitting. Issue 16 (12th April 2021) - Cai, Fengming; Liao, Liling; Zhao, Yang; Li, Dongyang; Zeng, Jinsong; Yu, Fang; Zhou, Haiqing
Abstract : Iron is a good enhancer for boosting the sluggish water and urea oxidation reactions with low potentials of 1.518 and 1.372 V, respectively, which further actualize 500 mA cm −2 at 1.623 and 1.472 V stably for water and urea electrolysis, respectively. Abstract : Designing highly active electrocatalysts for both the oxygen evolution and urea oxidation reactions (OER and UOR) with good durability at large current densities is very significant for greatly reducing the power consumption of water electrolysis and wastewater degradation. However, very few electrocatalysts simultaneously exhibit outstanding catalytic activities and large-current durability for both the oxygen evolution and urea oxidation reactions. Herein, we report a bifunctional nanoporous Fe-rich nitride hybrid electrocatalyst possessing extraordinary catalytic OER and UOR activities, as evidenced by extremely small potentials of 1.518 and 1.372 V with impressive long-term durability at a current density of 500 mA cm −2 for both OER and UOR in base, respectively. Thus far, this is one of the best electrocatalysts embedding excellent OER and UOR properties in a single electrocatalyst. In particular, combined with an efficient NiMoO4 –H2 catalyst for the HER, we have actualized the commercially viable current density of 500 mA cm −2 at 1.623 V and 1.472 V for overall water and urea electrolysis with outstanding long-term durability, respectively, outperforming most water or urea electrolysers reported hitherto. This work offers a novel approach to develop multifunctional electrocatalysts from earth-abundant elements for the energy-efficient hydrogen production and pollution treatment of urea-rich wastewater.